Making peace with nature: A scientific blueprint to tackle the climate, biodiversity and pollution emergencies - United Nations Environment Programme (2021)
This report presents a flexible scientific blueprint for how the climate change, biodiversity and pollution emergencies can be tackled jointly within the framework of the SDGs. The first of its kind, this report gathers expertise from across recent global assessments to gauge Earth’s environmental decline and suggest how society at large can best respond. The expert analysis synthesizes key findings from the assessments with those from additional high-impact peer-reviewed literature and grey literature. Part I of this report shows how the findings of the assessments are interlinked and add up to an unparalleled planetary emergency. It presents a diagnosis of how the human transformation of Earth’s natural systems puts the collective human future at risk.